New methodology of evaluating herbicide selectivity to sugarcane crop - Fagliari, Júlio Roberto (2008)
The present research aimed at evaluating the selectivity of herbicides applied to sugarcane, Saccharum spp (Poaceae), without interference from weeds and using twofold checks. Data were analyzed in two different ways: in the first case, areas treated with herbicides were compared to the average value of all twofold checks. In this case, which is the conventional method of study in selectivity, no herbicides affected either growth on yield characteristics, leading to the conclusion that all herbicides applied were selective to sugarcane. However, in the second way of analyzing data, when each herbicide was compared to the average values of its own twofold check, a quite different behavior of most herbicides was observed. The majority of the herbicides used was considered to be non selective to sugarcane crop